2023
DOI: 10.1186/s43088-023-00352-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal shape design of an airship based on geometrical aerodynamic parameters

Abstract: Background Conventional airship mathematical modeling usually involves six coupled degrees of freedom and two inputs, namely tail and thrust. The current study focuses on aerodynamic modeling. The aerodynamic model is developed in 3D-space based on plane semi-empirical model of a symmetric airship. The model depends on the main geometrical parameters of the airship. The study introduces an optimal shape design of the airship. The objective function is established to reduce drag and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Same conclusions were presented by Suiçmez [36]. These analyses led to use the first method of LQT controller with switching to the second method at the points of changing trajectory profile, see Figures 18,19…”
Section: Comparison Of Tracking Controllersmentioning
confidence: 57%
See 3 more Smart Citations
“…Same conclusions were presented by Suiçmez [36]. These analyses led to use the first method of LQT controller with switching to the second method at the points of changing trajectory profile, see Figures 18,19…”
Section: Comparison Of Tracking Controllersmentioning
confidence: 57%
“…The airship 3D model built by Atyya et al [19], shown in Figure 6, with hollow hull and tri-motors as a propulsive unit will be used in the current study.…”
Section: Airship Mass Propertiesmentioning
confidence: 99%
See 2 more Smart Citations